The position of the Lake Toba Authority Body is based on Presidential Regulation Number 49 of 2016 concerning the Lake Toba Tourism Area Management Authority Body - Augusto Edytama Prasetia; Siti Malikhatun Badriyah (Melayunesia Law, 2023)
The Lake Toba Tourism Authority Management Body was formed through Presidential Regulation Number 49 of 2016. After the formation of the Lake Toba Tourism Authority Body, many pros and cons occurred, apart from the issue of overlapping authority between the central government and regional governments regarding management rights, representatives of indigenous peoples also claimed that the Authority Body only carries out unilateral development without involving local indigenous peoples, besides that the agrarian problem of customary land in the Lake Toba area is also a fundamental problem, land and land which initially had no legal certainty and had become the land of local indigenous peoples were suddenly empowered to used for the Lake Toba Tourism Authority Board using the legal basis for Presidential Regulation Number 49 of 2016 concerning the Lake Toba Tourism Area Management Authority Body. The research method used in this study uses a normative research approach, while from the nature of this research it is a descriptive research.